PENGARUH INTERAKSI TEMAN SEBAYA TEHADAP PERILAKU SOSIAL SISWA KELAS XI IIS DI SMAN 2 PONTIANAK - Sari, Vika Yunika; Rustiyarso, Rustiyarso; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was aimed to find out the effect size of peer interaction on social behaviour of XI IIS students at SMAN 2 Pontianak. This research was conducted with a quantitative method. The technique of data collection were used indirect communication technique, direct communication technique and documentary studies. The tools of the data collection were questionnaire and notes. The sample of this research was 124 students of class XI IIS selected by using cluster random sampling. The result shows that peer interaction and social interaction were categorized as a medium where peer interaction has 64% and social behaviour has 97%. The research findings indicate that there was influence between peer interaction and social behavior. The result of hyphothesis shows that rcount (0.533) > rtable (0.175). The significant value was (0.00) < significant level (0.05). Regression equality Y = 20.903 + 0.445X shows that peer interaction increased one person then, the social behavior increased by 0.445. Adjusted R square determinant value was 0.278 which mean that the contribution of peer interaction to low social behaviour was 27,8% and 72,2% determine by other factors that have not been research.  Keywords: Peer Interaction, Social Behaviour,  Senior High School Students